Ultra-narrow low-bandgap graphene nanoribbons from bromoperylenes: synthesis and terahertz-spectroscopy - Jänsch, Daniel (2017)
Soluble ultra-narrow armchair graphene nanoribbons (AGNRs) with length of ≈20 nm and completely fused cores exceeding 5 nm in length, pronounced near-infrared (NIR) absorption up to 1400 nm, and a low band gap (≈0.9 eV) are synthesized from 3,9(3,10)-dibromoperylene and 3,4,9,10-tetrabromoperylene. Since the monomers are obtained from perylene carboxyanhydrides, a remarkable link between dye and graphene chemistry is established. The two-step protocol for the AGNR synthesis by aryl-aryl coupling and subsequent cyclodehydrogenation is compared with a direct Yamamoto polymerization. Ultrafast photoconductivity analysis by optical pump-terahertz (THz) probe spectroscopy of the longest AGNRs excited in the NIR regime (800 nm) reveal their high intrinsic charge carrier mobility.
First published: 20 March 2017
Gesehen am 25.06.2018